2021
DOI: 10.3390/su13179649
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Influencing Factors of the Romanian Agricultural Output within the Context of Green Economy

Abstract: The objective of this study is to analyze the trends in agriculture and the factors affecting the output of agriculture (OA) in the EU and Romania in the context of green economy. The research used the quantitative (mathematical regression function, correlation matrix, and R-squared) and qualitative (the SWOT matrix of the agriculture sector in Romania) methods. The data on Romanian agriculture were gathered from Eurostat for the period of 2006–2019. The results showed that there is a direct and positive relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
(40 reference statements)
1
3
0
Order By: Relevance
“…All this explains the negative influence that the AE1 indicator has on the evolution of the GDP. These results are in agreement with previous research that considers irrigation to be a factor that can contribute to an increase in agricultural production, and implicitly the contribution of agriculture to the GDP [ 37 , 55 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…All this explains the negative influence that the AE1 indicator has on the evolution of the GDP. These results are in agreement with previous research that considers irrigation to be a factor that can contribute to an increase in agricultural production, and implicitly the contribution of agriculture to the GDP [ 37 , 55 ].…”
Section: Resultssupporting
confidence: 92%
“…In a study that analyzes the factors that influence agricultural production in Romania [ 37 ], it was observed that one of the influencing factors was the level of irrigation norms (i.e., irrigation norm-translated) whose growth in Romania requires institutional, political and investment involvement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…So that everyone who can contribute to promoting the progress of GE is not discouraged but rather inspired to accept the new challenges and discover solutions to overcome the problems, the economic and social expenses of this transition must be spread. Governments alone may play this role by advocating for the necessary policies (S. Ali et al, 2020;Florea et al, 2021;Hafiza et al, 2022;Li et al, 2022;C. Shahid et al, 2023;Zhu, Fang, Rahman, & Khan, 2023;Zulfiqar et al, 2022).…”
Section: Long Run Panel Ardl Estimationmentioning
confidence: 99%
“…Cost-benefit analysis (CBA) is a decisionsupport tool to assess the welfare effects of a project or an investment (Hansjürgens, 2004). Green economy initiatives require investments and reduction of environmental costs (Florea et al, 2021;Watson, 2006). Market instruments, government regulations, levies, charges, taxes can scale up green economy investments, as well as internalise the environmental costs and social externalities (Pizzol et al, 2014).…”
Section: Zielone Finansowanie I Zielone Inwestycjementioning
confidence: 99%